2003
DOI: 10.1017/cbo9780511550256
|View full text |Cite
|
Sign up to set email alerts
|

Stable Modules and the D(2)-Problem

Abstract: This 2003 book is concerned with two fundamental problems in low-dimensional topology. Firstly, the D(2)-problem, which asks whether cohomology detects dimension, and secondly the realization problem, which asks whether every algebraic 2-complex is geometrically realizable. The author shows that for a large class of fundamental groups these problems are equivalent. Moreover, in the case of finite groups, Professor Johnson develops general methods and gives complete solutions in a number of cases. In particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
108
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(110 citation statements)
references
References 0 publications
2
108
0
Order By: Relevance
“…The class of such modules is tame in the sense of Johnson [8,Chapter 4], so that projective modules are relatively injective and Ext…”
Section: Preliminariesmentioning
confidence: 99%
See 2 more Smart Citations
“…The class of such modules is tame in the sense of Johnson [8,Chapter 4], so that projective modules are relatively injective and Ext…”
Section: Preliminariesmentioning
confidence: 99%
“…Accordingly, we say that the D(2) property holds for if every three dimensional complex with fundamental group isomorphic to , satisfying the hypothesis of the D(2) problem, is homotopy equivalent to a two dimensional complex. In [8], Johnson relates the D(2) problem to the realization problem as follows:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Johnson [8,Theorem IV,p 220] showed that the chain homotopy classes of algebraic 2-complexes of minimal Euler characteristic over Q 4n correspond to the isomorphism classes of rank 1 stably free ZQ 4n -modules. It is unknown whether the algebraic 2-complexes corresponding to stably free nonfree modules are geometrically realizable.…”
Section: Introductionmentioning
confidence: 99%
“…Major techniques for classifying the homotopy types of presentation complexes actually classify chain homotopy types of algebraic 2-complexes; see eg, Beyl-Latiolais-Waller [2], Browning [4], Johnson [8] and Sieradski-Dyer [16]. As long as Wall's D(2)-problem remains unresolved, a complete homotopy classification of 2-complexes requires that an actual presentation complex be constructed for each chain homotopy type.…”
Section: Introductionmentioning
confidence: 99%